The Study of Symbolic Interaction of Funeral Tradition on Ethnic Chinese in Lombok - Anthony Anggrawan; Mayadi Mayadi (Universitas Bumigora, 2020)
There are various burial cultures in Indonesia, including the Chinese ethnic burial culture. What is interesting in almost all burial cultures is the cultural heritage that has been passed down through generations. The question is how actually the ceremonial Chinese ethnic funeral ritual is, and what the symbols in the ethnic Chinese funeral ritual mean. This research provides an answer solution. This research is a qualitative research. The results of the study concluded that before the funeral ritual is carried out, younger family members pay their respects to the older deceased. During the funeral ritual, the next of kin accompany the vehicle carrying the body to the burial or cremation site, on foot, if the burial place is relatively close, or by vehicle if the burial place is far away. During the funeral, flowers, offerings, food and burnt incense are served. The culture of the Chinese funeral ritual was based on belief as a form of human relations with the creator of life and also as a way to maintain the symbol of family or relatives with the deceased and to bear the sins of the deceased.